TEKNIK DETEKSI DNA/GENE TARGET TERHADAP PATOGEN PENYEBAB PENYAKIT TANAMAN - HARYUNI HARYUNI (JURNAL ILMIAH AGRINECA, 2008)
Applications for detecting and Quantifying Transcripts to quantifyng viruses, pathogen detection, gene expression, drug theraphy, DNA damage, Immune response, genotyping.Methods in common use for detecting/quantifying transcrips are: 1) Northern blothing and in situ hybridization, 2) RNAse protection assays, 3)cDNA microarrays, 4) Reverse transciption-polymerase chain reaction.